PERTUMBUHAN BIBIT KARET STUM MATA TIDUR PADA MEDIA GAMBUT DENGAN INTERVAL PENYIRAMAN YANG BERBEDA - Sopiana, Sopiana; Ratnawati Hermanto, Sarwendah; Aprianingrum, Eni (Politeknik Negeri Ketapang, 2022)
Rubber is a latex-producing plant that has economic value in increasing people's income and welfare. The purpose of this study was to study the growth of sleeping eye stumps on peat media with different watering intervals. This research was conducted in the experimental garden of the Ketapang State Polytechnic, Delta Pawan District, Ketapang Regency, West Kalimantan from April to June. This study used a single factor Randomized Block Design (RAK) with 4 treatments and was repeated 5 times. K0: watering interval once a day, K1: watering interval every 2 days, K2: watering interval every 3 days, K3: watering interval every 4 days. The results showed that the once-a-day watering interval was optimum for the growth of rubber bed stumps on peat media.